A study on relationship between job promotion and job quality with job satisfaction among employees in Jabatan Agama Islam Selangor / Nurul Huda Zasali - Zasali, Nurul Huda (2016)
The purpose of this study is to determine the relationship between job promotion and job quality with job satisfaction among employees in Jabatan Agama Islam Selangor (JAIS). The scope of this study was involved the employees at Jabatan Agama Islam Selangor (JAIS). The total population for this research was 100 and a set of questionnaires was distributed to 80 employees at Jabatan Agama Islam Selangor. By SPSS 2.0 Statiscal Software, the data from the sample set was analysed. The questionnaire was developing in Bahasa Malaysia and English version and it was divided into 4 sections. Section A was the questionnaire analysed the demographic background of the respondents. Section B analysed the job promotion and job satisfaction components. Meanwhile, Section C was analysed job quality and job satisfaction. Lastly Section D it analysed about job satisfaction of employees in JAIS. The results obtained from the questionnaire, the findings showed that the job promotion and job quality has the relationship with job satisfaction.